Interpretable machine learning for predicting the fate and transport of pentachlorophenol in groundwater - Mehran Rad; Azra Abtahi; Ronny Berndtsson; Ursula S. McKnight; Amir Aminifar (Environmental Pollution, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Synergistic Impacts of Anthropogenic Stressors and COVID-19 on Aquaculture: A Current Global Perspective - G. Sarà; M. C. Mangano; M. Berlino; L. Corbari; M. Lucchese; G. Milisenda; S. Terzo; M. S. Azaza; J. M. F. Babarro; R. Bakiu; B. R. Broitman; A. H. Buschmann; et al. (Reviews in Fisheries Science & Aquaculture, 2022)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Early Exposure to Ketamine Impairs Axonal Pruning in Developing Mouse Hippocampus - Aleksandar Lj. Obradovic; Navya Atluri; Lorenza Dalla Massara; Azra Oklopcic; Nikola S. Todorovic; Gaurav Katta; Hari P. Osuru; Vesna Jevtovic-Todorovic (Molecular Neurobiology, 2018)

Differential response of terpenes and anthraquinones derivatives in Rumex dentatus and Lavandula officinalis to harsh winters across north-western Himalaya - Sumira Jan; Azra N. Kamili; Javid A. Parray; Yashbir S. Bedi (Natural Product Research, 2016)

Developmental cycle and host interaction of R habdochlamydia porcellionis , an intracellular parasite of terrestrial isopods - Barbara S. Sixt; Rok Kostanjšek; Azra Mustedanagic; Elena R. Toenshoff; Matthias Horn (Environmental Microbiology, 2013)
Summary Environmental chlamydiae are a diverse group of obligate intracellular bacteria related to well‐known pathogens of humans. To date, only very little is known about chlamydial species infecting arthropods. In this study, we used cocultivation with insect cells for recovery and maintenance of R habdochlamydia porcellionis , a parasite of the crustacean host P orcellio scaber . In vitro , the infection cycle of R . porcellionis was completed within 7 days, resulting in the release of infectious particles by host cell lysis. Lack of apoptosis induction during the entire course of infection, combined with a reduced sensitivity of infected cultures to experimentally induced programmed cell death, indicates that R . porcellionis like its human pathogenic relatives counteracts this host defence mechanism. Interestingly, the rod‐shaped variant of R . porcellionis , proposed to represent their mature infective stage, was not detected in cell culture, suggesting that its development may require prolonged maturation or may be triggered by specific conditions encountered only in the animal host. This first cell culture‐based system for the cultivation and investigation of an arthropod‐associated chlamydial species will help to better understand the biology of a so far neglected group of chlamydiae and its recently suggested potential to cause disease in humans.

Isolation and properties of methanesulfonate‐degrading Afipia felis from Antarctica and comparison with other strains of A. felis - S. Azra Moosvi; Catarina C. Pacheco; Ian R. McDonald; Paolo De Marco; David A. Pearce; Donovan P. Kelly; Ann P. Wood (Environmental Microbiology, 2005)
Summary Three novel strains of methylotrophic Afipia felis were isolated from several locations on Signy Island, Antarctica, and a fourth from estuary sediment from the River Douro, Portugal. They were identified as strains of the α‐2 proteobacterium A. felis by 16S rRNA gene sequence analysis. Two strains tested were shown to contain the fdxA gene, diagnostic for A. felis . All strains grew with methanesulfonate (and two strains with dimethylsulfone) as sole carbon substrate. Growth on methanesulfonate required methanesulfonate monooxygenase (MSAMO), using NADH as the reductant and stimulated by reduced flavin nucleotides and Fe(II). Polymerase chain reaction amplification of DNA from an Antarctic strain showed a typical msmA gene for the α‐hydroxylase of MSAMO, and both Antarctic and Portuguese strains contained mxaF , the methanol dehydrogenase large subunit gene. This is the first report of methanesulfonate‐degrading bacteria from the Antarctic and of methylotrophy in Afipia , and the first description of any bacterium able to use both methanesulfonate and dimethylsulfone. In contrast, the type strain of A. felis DSM 7326 T was not methylotrophic, but grew in defined mineral medium with a wide range of single simple organic substrates. Free‐living Afipia strains occurring widely in the natural environment may be significant as methylotrophs, degrading C 1 ‐sulfur compounds, including the recalcitrant organosulfur compound methanesulfonate.